1977
DOI: 10.1002/ijc.2910190503
|View full text |Cite
|
Sign up to set email alerts
|

Depressed in vitro peripheral blood lymphocyte response to mitogens in cancer patients: The role of suppressor cells

Abstract: The reactivity of peripheral blood lymphocytes from patients with advanced malignancy was assessed by mitogen-induced stimulation of protein synthesis as measured by 3H-leucine incorporation. It was confirmed that the lymphocyte response of patients was depressed. Furthermore, the lymphocytes of 15 out of 27 cancer patients, selected because of their low responses, inhibited the reactivity of normal lymphocytes in co-cultures. The lymphocytes from one patient with Hodgkin's disease were also inhibitory. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(38 citation statements)
references
References 33 publications
2
35
0
1
Order By: Relevance
“…In the blood cell cultures of all four groups of cancer patients, significantly lower values of IFN-gamma (P < 0.001), IL-2 (P < 0.01) and IL-1 alpha (P < 0.01) were found as compared to the controls, although lymphocyte and monocyte counts were almost identical.Grouping the tumour patients into different clinical stages we could show in the four groups of carcinomas a gradual depression of the cytokine production according to growing tumour burden.The host's response to malignant tumours is usually considered to be primarily a function of the cellular immune system and various tests have been established to measure the integrity of this system in cancer patients, such as hypersensitivity skin tests (Bolton et al, 1975;Evans et al, 1977), or determination of mitogen-induced lymphocyte proliferation in vitro (Dean et al, 1977;Zembala et al, 1977;Fritze & Dystant, 1984).As the cell-mediated immune response is controlled by a series of soluble cytokines, in recent years the measurement of these substances has also been used to determine the cellular immunological potency of tumour patients (Rey et al, 1983;Santos et al, 1985;Elsasser-Beile et al, 1991a Blood samples Ten ml of heparinised blood was taken from each patient and control person between 9 and 11 a.m. The samples, kept at room temperature, were used within 2 h. A 0.5 ml aliquot was removed for total and differential leukocyte counts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the blood cell cultures of all four groups of cancer patients, significantly lower values of IFN-gamma (P < 0.001), IL-2 (P < 0.01) and IL-1 alpha (P < 0.01) were found as compared to the controls, although lymphocyte and monocyte counts were almost identical.Grouping the tumour patients into different clinical stages we could show in the four groups of carcinomas a gradual depression of the cytokine production according to growing tumour burden.The host's response to malignant tumours is usually considered to be primarily a function of the cellular immune system and various tests have been established to measure the integrity of this system in cancer patients, such as hypersensitivity skin tests (Bolton et al, 1975;Evans et al, 1977), or determination of mitogen-induced lymphocyte proliferation in vitro (Dean et al, 1977;Zembala et al, 1977;Fritze & Dystant, 1984).As the cell-mediated immune response is controlled by a series of soluble cytokines, in recent years the measurement of these substances has also been used to determine the cellular immunological potency of tumour patients (Rey et al, 1983;Santos et al, 1985;Elsasser-Beile et al, 1991a Blood samples Ten ml of heparinised blood was taken from each patient and control person between 9 and 11 a.m. The samples, kept at room temperature, were used within 2 h. A 0.5 ml aliquot was removed for total and differential leukocyte counts.…”
mentioning
confidence: 99%
“…The host's response to malignant tumours is usually considered to be primarily a function of the cellular immune system and various tests have been established to measure the integrity of this system in cancer patients, such as hypersensitivity skin tests (Bolton et al, 1975;Evans et al, 1977), or determination of mitogen-induced lymphocyte proliferation in vitro (Dean et al, 1977;Zembala et al, 1977;Fritze & Dystant, 1984).…”
mentioning
confidence: 99%
“…(1976). It is reported that the depressed response to phytohaemagglutinin and in the MLC of blood lymphocytes in some cancer patients is due to the presence of suppressor cells, even though the total E-RFC is within the normal range (Berlinger et al, 1976;Zembala et al, 1977;Quan & Burtin, 1978). Thus the level of 4°C E-RFC does not always correlate well with the clinical and immune status of patients with malignant diseases.…”
Section: C E-rfcmentioning
confidence: 99%
“…Investigations in several solid tumour systems have demonstrated that presence of tumour is associated with a reduction of nonspecific cell-mediated immunity (CMI) as demonstrated by skin testing with ubiquitous antigens (Burdick et al, 1976) and lymphocyte blastogenesis with phytomitogens (Zembala et al, 1977;Jun et al, 1979). On the other hand, the presence of tumour is associated with the appearance of specific CMI responses to tumour antigens, as shown by a variety of in vivo (Pellis & Kahan, 1976) and in vitro methods (Baldwin & Embleton, 1977;Jun et at., 1979;Halliday et at., 1977).…”
mentioning
confidence: 99%
“…This contrasts with the studies of Halliday et al (1975Halliday et al ( , 1977, and Maluish (1979) in which specific LAI reactivity against tumour antigens was detected regardless of the stage to which the tumour had progressed. Where reduction of specific reactivity has been reported it may reflect general suppression of CMI (Jun et al, 1979), blocking factors (Baldwin & Price 1976; Bowen et al, 1975) cellular suppressive activity (Zembala et al, 1977) elaboration of soluble suppressor products by the tumour itself (Delustro & Argyris, 1976) or combinations of these.…”
mentioning
confidence: 99%